2014
DOI: 10.1111/1750-3841.12371
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme‐Treated Asparagus Extract Promotes Expression of Heat Shock Protein and Exerts Antistress Effects

Abstract: A novel enzyme-treated asparagus extract (ETAS) has been developed as a functional material produced from asparagus stem. Studies were conducted to determine the effect of ETAS on heat shock protein 70 (HSP70) expression and alleviation of stress. HeLa cells were treated with ETAS, and HSP70 mRNA and protein levels were measured using a reverse transcription-polymerase chain reaction (RT-PCR) assay and an enzyme-linked immunosorbent assay (ELISA), respectively. ETAS showed significant increases in HSP70 mRNA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 33 publications
1
35
2
Order By: Relevance
“…In an animal study, we found that ETAS suppressed blood corticosterone elevation, as well as up-regulated HSP70 protein levels of the stomach, liver and kidney, in mice subjected to sleep deprivation when given ETAS (15). Other investigators have reported that ETAS shows neuroprotective effects in vitro and attenuates cognitive impairment in senescence-accelerated mice (17).…”
Section: Effects Of Enzyme-treated Asparagus Extract On Heat Shock Prmentioning
confidence: 69%
See 2 more Smart Citations
“…In an animal study, we found that ETAS suppressed blood corticosterone elevation, as well as up-regulated HSP70 protein levels of the stomach, liver and kidney, in mice subjected to sleep deprivation when given ETAS (15). Other investigators have reported that ETAS shows neuroprotective effects in vitro and attenuates cognitive impairment in senescence-accelerated mice (17).…”
Section: Effects Of Enzyme-treated Asparagus Extract On Heat Shock Prmentioning
confidence: 69%
“…Since the previous study revealed that ETAS significantly increased HSP70 expression level in mice and humans (15), a bigger sample size might be necessary for the current detection procedure. ETAS improved several parameters of the autonomic nervous system (ANS) condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A human study also demonstrated that serum and salivary cortisol levels in subjects receiving ETAS were lower than those in the placebo group [2]. These anti-stress effects of ETAS are associated with the induction of molecular chaperones such as heat shock protein 70 [1][2][3].…”
mentioning
confidence: 98%
“…Growing evidence indicates that enzyme-treated asparagus extract (ETAS) from the unused bottom parts of asparagus (Asparagus officinalis) exhibits a wide variety of beneficial biological actions. For example, intake of ETAS attenuates the elevation of plasma corticosterone levels in sleep-deprived mice [1]. A human study also demonstrated that serum and salivary cortisol levels in subjects receiving ETAS were lower than those in the placebo group [2].…”
mentioning
confidence: 99%